2006
DOI: 10.1055/s-2005-922014
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Endonasal Partial Middle Turbinectomy Approach: Adaptability of the Procedure in a Cadaveric Study and in Surgery for Different Sphenoid Sinus and Skull Base Lesions

Abstract: Objective: To demonstrate the flexibility, adaptability, and efficacy of endoscopic endonasal removal of the inferior half of the middle turbinate in a cadaveric study and in surgery for the treatment of different sphenoid sinus and skull base lesions. Methods: Anatomic Cadaveric Study: Five adult cadaveric heads were studied. Six nostrils of 3 cadavers were studied endoscopically after the lower half of the middle turbinate was removed. Two adult cadaveric heads underwent bilateral paraseptal sagittal section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
(52 reference statements)
0
16
0
2
Order By: Relevance
“…Carrabba et al (2) reported that the incidence of CSF leakage was 24% after EEA. Therefore, the reconstruction of skull base defect is of paramount importance to prevent CSF leakage after endoscopic endonasal surgery (9,11). A pedicled mucosal flap is one of the major advancements in endoscopic endonasal skull base reconstruction, which is regarded by most authors as the best method to repair a defect of the skull base (11,14,15,21,23).…”
Section: Discussionmentioning
confidence: 99%
“…Carrabba et al (2) reported that the incidence of CSF leakage was 24% after EEA. Therefore, the reconstruction of skull base defect is of paramount importance to prevent CSF leakage after endoscopic endonasal surgery (9,11). A pedicled mucosal flap is one of the major advancements in endoscopic endonasal skull base reconstruction, which is regarded by most authors as the best method to repair a defect of the skull base (11,14,15,21,23).…”
Section: Discussionmentioning
confidence: 99%
“…7 Therefore, the reconstruction of skull base defect is of paramount importance to prevent CSF leakage after endoscopic endonasal surgery. 8,9 In patients with large dural defects of anterior and ventral skull base, there is a significant risk of post-operative cerebrospinal fluid (CSF) leak after reconstruction. Reconstruction with vascularised tissue is desirable to facilitate rapid healing, especially in irradiated patients.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, surgical management is best optimized using a multidisciplinary team consisting of neurosurgeons and otolaryngologists. [1][2][3][4][5] Endoscopic endonasal reconstruction of skull base defects for sealing of CSF rhinorrhea or following tumor resection is of paramount importance in avoiding serious and life-threatening complications (e.g., meningitis, encephalitis, or a cerebral abscess). [2][3][4][5] In the current study, we used the endoscopic endonasal partial middle turbinectomy approach 5 in most of the surgeries; besides the wider surgical field created by this approach, the harvested piece of turbinate obtained was used in repairing the skull base defect.…”
Section: Discussionmentioning
confidence: 99%